Clinical significance of osteoprotegerin expression in human colorectal cancer - Tsukamoto, Shunsuke; Ishikawa, Toshiaki; Iida, Satoru; Ishiguro, Megumi; Mogushi, Kaoru; Mizushima, Hiroshi; Uetake, Hiroyuki; Tanaka, Hiroshi; Sugihara, Kenichi (Clinical cancer research, 2011)
This study aimed to identify a novel biomarker or a target of treatment for colorectal cancer (CRC). The expression profiles of cancer cells in 104 patients with CRC were examined using laser microdissection and oligonucleotide microarray analysis. Overexpression in CRC cells, especially in patients with distant metastases, was a prerequisite to select candidate genes. The mRNA expression of candidate genes was investigated by quantitative reverse transcriptase PCR (RT-PCR) in 77 patients as a validation study. We analyzed the protein expression and localization of the candidate gene by immunohistochemical study and investigated the relationship between protein expression and clinicopathologic features in 274 CRC patients. Using microarray analysis, we identified 6 candidate genes related to distant metastases in CRC patients. Among these genes, osteoprotegerin (OPG) is known to be associated with aggressiveness in several cancers through inhibition of apoptosis via neutralization of the function of TNF-related apoptosis-inducing ligand. The mRNA expression of OPG in cancer tissues was significantly higher in patients with distant metastases than those without metastases. Overexpression of OPG protein was associated with significantly worse overall survival and relapse-free survival. Moreover, overexpression of the OPG protein was an independent risk factor for CRC recurrence. Overexpression of OPG may be a predictive biomarker of CRC recurrence and a target for treatment of this disease.